Analisis Penyebab Cacat Produk Truck Body 777 Pada Aktifitas Painting - Ganda Sirait (Universitas Putera Batam, 2018)
Painting activity is a production process that determines the quality of the company's products. This painting process is an application in liquid form, to create a layer for later, a hard layer or cat layer. Product defects from painting activities that are still found by the availability of paint on the product, it is a challenge to provide the company the best solution. Another problem is the number of cats used by the production department in the painting process. Supply chain issues in inventory inventory of painting materials, sometimes stocks and stocks runs out. This study will discuss and analyze the factors that find the number of cats in the painting Truck Body 777 performs Cuase and Effect analysis (fishbone diagram) and uses Analytical Hierarchy Process (AHP) to determine the cat's glory factor. Data is taken from production data for one year and four months. Result of research result from every factor of production, cause of product defect in percentage, that is human being equal to 65%, method equal to 62%, machine equal to 48%, material equal to 75%, and environment 50%, and also highest dominant factor difference the amount of paint used in the 777 Truck Body process is a material factor